Analysis of the Causes of Potential Failure on the Critical Path Using Fmea for Project Bag Case Packer In Robotic Machinery Automation Manufacturing Companies - MM, Safaat; NUZULUL FATIMAH (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
This study aims to determine the potential failures that occur in the critical trajectory path in a packaging machine manufacturing project, which can provide information to the project managers in preventing risks that can occur at the machine manufacturing stage that are included in the critical path lane. This research uses mixed research methods that is, a general type of research which quantitative and qualitative methods are mixed in one overall study. The sample used in this study is the section head in each division who participates in the machine production process which will then be analyzed using the Failure Mode and Effects Analysis (FMEA) method where previously it was determined that the stage of making machines that entered the critical trajectory path using Ms. project software. The results of this study are known that there are eleven stages of machine manufacturing that are included in the critical path where there are 5 potential failures with the highest RPN (Risk Priority Number) value. Thus it can be a target of project management in project planning to minimize the risks that will occur.